Highly Pathogenic Avian Influenza A(H5N1) Virus Infection in Cats, South Korea, 2023 - Yong-Myung Kang; Gyeong-Beom Heo; Se-Hee An; Hyunho Lee; Eunhye Park; Ra Mi Cha; Yun Yueng Jang; Mingeun Sagong; Ah-Young Kim; Jongho Kim; Eun-Kyoung Lee; Seong Hee Kim; et al. (Emerging Infectious Diseases)
In July 2023, cases of highly pathogenic avian influenza (HPAI) were reported at 2 shelters for stray cats in Seoul, South Korea. The cause of infection was suspected to be improperly sterilized raw food made from domestic duck meat, which was manufactured in South Korea. All viruses isolated from cats at the shelters and from the raw food belonged to HPAI A(H5N1) clade 2.3.4.4b. The gene constellation of all viruses was most similar to that of viruses isolated in Korea in November 2022. Of note, the viruses isolated from infected cats harbored mutations E627K or D701N in polymerase basic 2, which are indicative of adaptation to mammals. Postmortem examination revealed systemic pathologic lesions and the presence of widespread virus in different tissues. Thus, consumption of raw duck meat contaminated with HPAI virus likely caused systemic symptoms and death in cats, indicating the introduction of mammal-adapted mutations of the virus.